2022
DOI: 10.9734/ijecc/2022/v12i1030773
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sulphur and Zinc on Growth and Yield of Cowpea (Vigna unguiculata L.)

Abstract: Aim: To study the retaliation performances of Sulphur and zinc on growth, yield and yield attributes of cowpea (Vigna unguiculate L.) Place and Duration of Study A field experiment was carried out during kharif season of 2021 at Crop Research Farm, Sam Higginbottom University of Agriculture, Technology and Sciences, Prayagraj Uttar Pradesh, India.    Methodology: The Experiment was laid out in Randomized Block Design with Ten treatments which were replicated thrice. with treatment combination of (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
3
3
0
Order By: Relevance
“…The increased gross returns, net returns and benefit: cost ratio was due to increased seed and stover yield under foliar application of Sulphur 4% with zinc at 1.5%. The findings are in close conformity with those of Durugude et al [18][19][20][21][22][23][24].…”
Section: Economicssupporting
confidence: 92%
“…The increased gross returns, net returns and benefit: cost ratio was due to increased seed and stover yield under foliar application of Sulphur 4% with zinc at 1.5%. The findings are in close conformity with those of Durugude et al [18][19][20][21][22][23][24].…”
Section: Economicssupporting
confidence: 92%
“…The significant and higher plant height was with application of Sulphur (30kg/ha) as play important role in several physiological and biochemical processes which are of vital importance for growth and development of plant. Similar findings also reported by Yadav et al [2]. Further, higher plant height was found that molybdenum (15 ppm) increases availability of nitrogen which helps in process of nitrogen assimilation.…”
Section: Plant Height (Cm)supporting
confidence: 89%
“…In India pulses are grown nearly in 25.43 m ha with an annual production of 17.20 m t and a median productivity of 679 kg/ha. The per capita availability of pulses in India is 35.5 g/day as against the minimum requirement of 70 g/day" [2]. "Cowpea grown across the world on an area 14.5 m ha of land planted each year and the total annual production is 6.2 m t. In India during 2020-21 cowpea is grown in about 13.3 m ha with an annual production of 8.06 m t and productivity of 596 kg/ha.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Application of Zn at 0 kgha -1 recorded higher LAR than 2.5 and 5 kgha -1 with an exception of the combined effect of the two years. This finding correlated with the work of Akay (2011) and Bozoglu et al (2007), who reported during their different studies on effect of zinc fertilization on chickpea varieties, another legume, that 0 kgha -1 induced higher LAR than higher doses (Yadav et al, 2022). The finding that the control (Zn 0 kgha -1 ) had higher LAR than the higher levels of 2.5 and 5 kgha -1 application in this work, is not in consistent with what zinc had been known to induce on growth parameters.…”
Section: Effects Of Year Phosphorus Zinc and Interactions On Lai Of D...supporting
confidence: 88%